A study on the relationship between waist phenotype, hypertriglyceridemia, coronary artery lesions and serum free fatty acids in adult and elderly patients with coronary diseases - Rui-Feng Yang; Hanlei Zhang; Zhongchun Wang; Xiao-Yong Liu; Zhi Lin (Immunity & Ageing, 2018)
Abstract Background Abdominal obesity is an independent risk factor for coronary heart disease (CHD) and high serum triglyceride (TG) and free fatty acid levels may precipitate or aggravate CHD. Methods We enrolled patients with coronary heart disease in our hospital from October 2008 to July 2009. Patients with high TG and increased WC, i.e. waist phenotype WP were included in group A. In group B, were included patients with high TG but not WP. Group C consisted of patients with WP but not high TG. Finally, Group D was composed of patients without high TG or WP. Serum FFA levels for all patients were measured by ELISA. The relationship between TG levels, WC, FFA levels, and coronary artery score was analysed by a single variable regression. Results Group A had a significantly higher FFA level than the other groups. Regression analysis showed that FFA, TG, WC, hip circumference, waist-to-height ratio, systolic blood pressure, pulse pressure index, and low-density lipoprotein cholesterol all positively correlated with CAS (r = 0.160 ~ 0.415, P = 0.000 ~ 0.032). After we controlled for traditional risk factors for cardiovascular disease, FFA levels remained positively correlated to the CAS (r = 0.365, P < 0.001). Conclusion The serum FFA level for patients with complications of both increased WC and high TG levels was significantly higher than that of patients without either of these complications. The close correlation between the CAS and FFA levels showed by regression analysis suggested that inflammation in these patients was more serious. Increased WC and high TG levels as well as FFA level are valuable for the prediction of cardiovascular disease and can be applied as a clinical guidance for early intervention in the treatment of coronary heart diseases.